Individual and organizational characteristics of women in managerial leadership - Rowney, J. I. A. (Journal of business ethics, 1990)
Women are making a substantial impact on the employment market, both in terms of overall numbers as well as by appointment to male-dominated organizational roles. Research on women in leadership positions within organizations has concentrated on two main foci. Firstly, the identification of relevant individual and organizational characteristics and secondly, on the impact of these variables on the women in management roles. This paper presents the findings from a series of studies in relation to these broad dimensions.